Danish Reactions to German Occupation History and Historiography - Holbraad, Carsten (UCL Press, 2017)
For five years during World War II, Denmark was occupied by Germany. While the Danish reaction to this period of its history has been extensively discussed in Danish-language publications, it has not until now received a thorough treatment in English. Set in the context of modern Danish foreign relations, and tracing the country's responses to successive crises and wars in the region, Danish Reactions to German Occupation brings a full overview of the occupation to an English-speaking audience. Holbraad carefully dissects the motivations and ideologies driving conduct during the occupation, and his authoritative coverage of the preceding century provides a crucial link to understanding the forces behind Danish foreign policy divisions. Analysing the conduct of a traumatised and strategically exposed small state bordering on an aggressive great power, the book traces a development from reluctant cooperation to active resistance. In doing so, Holbraad surveys and examines the subsequent, and not yet quite finished, debate among Danish historians about this contested period, which takes place between those siding with the resistance and those more inclined to justify limited cooperation with the occupiers - and who sometimes even condone various acts of collaboration